Myeloid PTEN deficiency impairs tumor-immune surveillance via immune-checkpoint inhibition. (2nd July 2016) - Kuttke, M.; Sahin, E.; Pisoni, J.; Percig, S.; Vogel, A.; Kraemmer, D.; Hanzl, L.; Brunner, J. S.; Paar, H.; Soukup, K.; Halfmann, A.; Dohnal, A. M.; et al.
ABSTRACT: Tumor–host interaction is determined by constant immune surveillance, characterized by tumor infiltration of myeloid and lymphoid cells. A malfunctioning or diverted immune response promotes tumor growth and metastasis. Recent advances had been made, by treating of certain tumor types, such as melanoma, with T-cell checkpoint inhibitors. This highlights the importance of understanding the molecular mechanisms underlying the crosstalk between tumors and their environment, in particular myeloid and lymphoid cells. Our aim was to study the contribution of the myeloid PI3K/PTEN-signaling pathway in the regulation of tumor-immune surveillance in murine models of cancer. We made use of conditional PTEN-deficient mice, which exhibit sustained activation of the PI3K-signaling axis in a variety of myeloid cell subsets such as macrophages and dendritic cells (DCs). In colitis-associated colon cancer (CAC), mice deficient in myeloid PTEN showed a markedly higher tumor burden and decreased survival. We attributed this observation to the increased presence of immune-modulatory conventional CD8α + DCs in the spleen, whereas other relevant myeloid cell subsets were largely unaffected. Notably, we detected enhanced surface expression of PD-L1 and PD-L2 on these DCs. As a consequence, tumoricidal T-cell responses were hampered or redirected. Taken together, our findings indicated an unanticipated role for the PI3K/PTEN-signaling axis in the functional regulation of splenic antigen-presenting cells (APCs). Our data pointed at potential, indirect, tumoricidal effects of subclass-specific PI3K inhibitors, which are currently under clinical investigation for treatment of tumors, via myeloid cell activation.